Engaging Europe: Rethinking a Changing Continent - Gould, Evlyn; Sheridan, George J. (Rowman & Littlefield Publishers, 2005)
What and where and who is Europe? This unique collection contends that Europe cannot be defined as simply a particular geographic location or a group of citizens who inhabit the same place and share a culture. Instead, Europe is a question to be answered by the teachers and students who study it. A collaborative and multidisciplinary collection, Engaging Europe explores Europe through history, literature, philosophy, music, and ethical narratives. A set of imaginative contributors investigates European identity through a variety of cases, including Greece and Rome, the Bible, the Enlightenment, and the Shoah. Scholars of literature, history, and classics, as well as a composer, grapple with students' doubts about Europe's future relevance. The complexity of the topic leads to creativity in each chapter, from a musical composition in words to poetry to a dialogue between Baudelaire and Adam Smith. Engaging Europe is a major part of an experiment that hopes to find more intellectually exciting ways to teach Europe to students in American higher education. Contributions by: Evlyn Gould, Joseph Krause, Robert Kyr, Massimo Lollini, Alexander B. Murphy, John Nicols, Steven Shankman, George J. Sheridan Jr., and Malcolm Wilson